2020
DOI: 10.1111/ejss.12979
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic and functional analysis of soil microbial communities in a mining site across a metal(loid) contamination gradient

Abstract: Soil microorganisms surviving in mining sites have developed metalresistance mechanisms to biotransform metals. Their use as biofertilizers can improve phytoremediation efficiency in contaminated soils by reducing metal toxicity while promoting plant growth. We analysed through wholemetagenome shotgun sequencing the composition, diversity and function of microbial communities present in a contaminated mine soil along a gradient of metals (As, Cu, Fe, Mn, Pb, Zn) to identify tolerant species carrying metal-resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 77 publications
1
5
0
Order By: Relevance
“…By cooperating or cross-feeding with other soil bacterial species, Actinobacteria are able to continue their metabolic activities even at low temperatures 53 . According to a study by Navas et al 54 , Actinobacteria are widely distributed in soils with low metal(loid) contamination.
Figure 6 Heatmap presenting differences in the relative abundance of particular sequences among all obtained sequences between the not enriched (control) and the halloysite-enriched soil samples, respectively (class level Euclidean distance measure, Ward algorithm used for clustering).
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…By cooperating or cross-feeding with other soil bacterial species, Actinobacteria are able to continue their metabolic activities even at low temperatures 53 . According to a study by Navas et al 54 , Actinobacteria are widely distributed in soils with low metal(loid) contamination.
Figure 6 Heatmap presenting differences in the relative abundance of particular sequences among all obtained sequences between the not enriched (control) and the halloysite-enriched soil samples, respectively (class level Euclidean distance measure, Ward algorithm used for clustering).
…”
Section: Resultsmentioning
confidence: 99%
“…and Sphingomonas sp. thrive in PTE-contaminated soils 54 , 59 , likely due to their PTE resistance genes 61 , 62 .…”
Section: Resultsmentioning
confidence: 99%
“…In freeze–thaw-exposed samples, abundances of Gammmaproteobacteria and Alphaprotepbacteria significantly increased, the abundance of Betaproteobacteria did not change and the average abundance of Deltaproteobacteria decreased. A study by Navas et al [ 95 ] has shown that Proteobacteria predominated in soil with a high content of metal(-loid)s while Actinobacteria were more abundant in soil with low content of metal(-loid)s. The higher resilience of Proteobacteria to high content of metal(-loid)s can be related to the fact that they are Gram-negative bacteria and possess an outer lipopolysaccharide layer in their cell wall that sequestrates metals extracellularly conferring adaptation to harsh contaminated environments [ 96 ]. Actinobacteria are an important member of soil microbiome participating in carbon cycling and production of soil organic matter [ 94 , 97 ].…”
Section: Resultsmentioning
confidence: 99%
“…Both genera were reported in soils contaminated with potentially toxic elements. Navas, et al [ 95 ] identified Mycobacterium sp. as a predominant genus in soil from mining sites but with a low content of potentially toxic elements while Sphingomonas sp.…”
Section: Resultsmentioning
confidence: 99%
“…Arsenic is typically present as arsenite (As(III)) in soils, and bacteria can pump out As(III) via an efflux pump, or reduce less common forms of arsenic to As(III) [ 66 ]. Furthermore, another study showed that the most abundant metal-resistance genes in soils from an abandoned copper mine were associated with Cu, As, and Fe resistance [ 67 ]. Nonetheless, a silver-lead–zinc mine also reported the soil bacterial community to vary with As concentrations [ 55 ].…”
Section: Discussionmentioning
confidence: 99%